A General Analysis Of Ali Al-Qari’s Scholarly Legacy - Usmanov Mukhtorjon Tursunali ogli (Open Academia, 2025)
This article presents a general analysis of the scholarly legacy of Ali al-Qari, a distinguished Islamic scholar of the 11th century AH. Renowned for his prolific authorship across diverse disciplines, Ali al-Qari made lasting contributions to Hadith studies, jurisprudence, theology (kalam), Qur’anic sciences, Sufism, and Arabic literature. The article highlights the breadth and accessibility of his works, particularly his method of writing clear and comprehensible commentaries that made complex texts understandable to a wider audience. Special attention is given to his major works such as Mirqat al-Mafatih, Sharh alFiqh al-Akbar, and Irshad al-Sari, which are still widely read and used in Islamic institutions today. His firm defense of the Hanafi school and his respectful yet critical engagement with differing scholarly opinions are also explored. Ultimately, the article underscores the enduring relevance of Ali al-Qari's intellectual legacy for contemporary Islamic scholarship
Keywords: Ali al-Qari; Islamic scholarship; Hadith commentary